2020
DOI: 10.1186/s10194-020-01197-0
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen receptors α, β and GPER in the CNS and trigeminal system - molecular and functional aspects

Abstract: Background Migraine occurs 2–3 times more often in females than in males and is in many females associated with the onset of menstruation. The steroid hormone, 17β-estradiol (estrogen, E2), exerts its effects by binding and activating several estrogen receptors (ERs). Calcitonin gene-related peptide (CGRP) has a strong position in migraine pathophysiology, and interaction with CGRP has resulted in several successful drugs for acute and prophylactic treatment of migraine, effective in all age gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
52
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 62 publications
(55 citation statements)
references
References 54 publications
1
52
0
2
Order By: Relevance
“…We are currently focused on identifying which nuclear and/or membrane estrogen receptors (ERα, ERβ, or GPER) are involved in potentiating the effects of 5HT on trigeminal sensory neurons. Previous studies have reported that ERα, ERβ, and GPER are present in trigeminal sensory neurons ( Chen et al, 2021 , Warfvinge et al, 2020 ).…”
Section: Discussionmentioning
confidence: 94%
“…We are currently focused on identifying which nuclear and/or membrane estrogen receptors (ERα, ERβ, or GPER) are involved in potentiating the effects of 5HT on trigeminal sensory neurons. Previous studies have reported that ERα, ERβ, and GPER are present in trigeminal sensory neurons ( Chen et al, 2021 , Warfvinge et al, 2020 ).…”
Section: Discussionmentioning
confidence: 94%
“…As the ion channels are downstream of both the CGRP receptor and G i -coupled receptors, they might prove more efficient in blocking the hypersensitivity and pain. In addition, to fully understand the nonresponders, we need to understand factors such as migraine chronification [15] and hormonal influence on migraine pathology [91,92].…”
Section: Concluding Remarks and Future Perspectivesmentioning
confidence: 99%
“… 16 Some studies have shown that estrogen and its nuclear receptors (ERα and ERβ) play a critical role in pain regulation. 17 , 18 , 19 , 20 However, few reports have directly investigated estrogenic effects on the descending pain modulation system, especially the function of GPER in the RVM on the chronification of postoperative pain.…”
Section: Introductionmentioning
confidence: 99%